Larvacidal activity of Illicium verum ethanolic extract against Aedes aegypti - Kurniawan, Betta; Saftarina, Fitria; Mustofa, Syazili; Syaka, Muthiiah Khodista (Universitas Aisyah Pringsewu, 2025)
Background: Chemical larvicides that have been used for a long time carry some risks by causing environmental risk. Besides, temephos has been documented to have the growth of resistance in various regions throughout the world among mosquito populations, consequently decreasing its effectiveness in eliminating the larval stage. Therefore, developing alternative plant-based larvicides was considered a worthy step to reduce the risk of resistance to chemical larvicides. Illicium verum (IV), a plant-based spice, contains secondary metabolites such as flavonoids, saponins, tannins, and alkaloids acting as larvicidal agents. This study was conducted to attain Illicium verum ethanolic extract as an alternate plant-based mosquito larvicide against the dengue vector Aedes aegypti.Methods: The research design was an experimental method with a post-test-only control group design. The larvicide test in this study was divided into five groups with four repetitions and analyzed by Kruskal-Wallis test, post-hoc Mann-Whitney test, and probit analysis conducted with 95% confidence interval.Results: No significant difference was shown between concentrations of 0.25%, 0.125%, and 1% temephos, which showed a value of p0.05 on the Mann-Whitney test. The probit test showed the LC50 value was 0.476%, and the LC90 value was 2.42% at the maximum observation time. At the highest concentration, the LT50 value was 0.037 hours, and the LT90 value was 0.269 hours.Conclusion: This study reveals that natural substance of Illicium verum ethanolic extract surpassed 1% temephos as a botanical larvicide against Aedes aegypti larvae. This should be an environment-friendly solution to synthetic larvicide resistance.